KORELASI GAYA MENGAJAR GURU AKUNTANSI DENGAN HASIL BELAJAR SISWA AKUNTANSI DI SMK NURUL FALAH PEKANBARU PEKANBARU - Devi krisna mustika; Suarman Suarman; R M Riadi R M Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This study aims to determine the correlation between the teaching style of accounting teachers and the learning outcomes of accounting students at SMK Nurul Falah Pekanbaru. The number of samples used in this study were 50 students. Types of data used in this study are primary data in the form of teacher teaching styles and secondary data from the value of student learning outcomes. The method of collecting data using a questionnaire. The analysis technique used in this research is descriptive and correlation test. The results showed that there was a significant relationship between the teaching style of accounting teachers and the learning outcomes of accounting students at SMK Nurul Falah Pekanbaru.Key Words: Teaching Style and Learning Outcomes